KESADARAN HUKUM MASYARAKAT TERHADAP PERCERAIAN DI DEPAN SIDANG MAHKAMAH SYAR’IYAH BLANGKEJEREN - juandi juandi; jamhuri jamhuri; syahrizal Abbas (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2024)
In the community of Blangkejeren District, Gayo Lues Regency, divorces are still found outside the Syar'iyah Court even though Law no. 16 of 2019 and the Compilation of Islamic Law have determined that every divorce must be carried out before a court hearing. Therefore, the main problem in this research is why people in Blangkejeren District divorce outside the Syar'iyah Court hearing and what is the level of legal awareness of the people in Blangkejeren District who divorce before the Syar'iyah Court hearing. Each research is expected to provide certain benefits, both theoretically and practically. The benefits of this research are theoretically useful for the development of science, for practitioners at the Sharia Court, and society. This research uses normative legal research methods (normative juridical) and sociological legal research (empirical juridical). The nature of this research is analytical descriptive, meaning a data analysis based on general legal theory applied to explain other data sets. To obtain accurate and relevant data, data collection was carried out using normative empirical methods. This research was conducted in Blangkejeren District, Gayo Lues Regency regarding public legal awareness regarding divorce before the Syar'iyah Court trial. Where public awareness is considered to be relatively high, this is proven by the behavior of the people of Blangkejeren District who take care of their divorce certificates. However, there are still people who are reluctant to apply for a divorce certificate due to factors such as public legal awareness, understanding of legal rules that have been ingrained since childhood, the separation between religious rules and state rules, requiring quite a long time, and the weak economic conditions of the community.